In between the Cosmos and “Thousand-Cubed Great Thousands Worlds”: Composition of Uncommon Worlds by Alexander von Humboldt and King Mongkut - Morita, Atsuro (Anthropologica, 2017)
Recent scholarship on Indigenous politics has illuminated the complex entanglements of science, bureaucracy, social movements and cosmological practices that tend to occur wherever Indigenous practices meet modern environmental management. These studies have shown how the powerful operations of science and bureaucracy, instantiating Western ontology, have eliminated Indigenous ontologies from public arenas such as those of policy-making. The reductive power of a modern ontology that assumes a “one-world world,” to borrow John Law’s (2011) word, is abundantly visible in these ethnographies of ontological encounters. Focusing on some nineteenth-century Thai episodes, occurring at the time when the modern one-world world was still being constructed in the form of new scientific infrastructures of observation, this article examines some of the ontological consequences of these encounters.